Start-up nation the story of Israel's economic miracle - Senor, Dan. (New York Twelve, 2009)
START-UP NATION addresses the trillion dollar question: How is it that Israel-- a country of 7.1 million, only 60 years old, surrounded by enemies, in a constant state of war since its founding, with no natural resources-- produces more start-up companies than large, peaceful, and stable nations like Japan, China, India, Korea, Canada and the UK?
"A Council on Foreign Relations book."
Keywords: Israel--Economic conditions